Cults and new religions : a brief history - Cowan, Douglas E.; Bromley, David G. (Chichester, West Sussex ; Malden, MA : Wiley Blackwell, 2015)
'This unparalleled introduction to cults and new religious movements has been completely up-dated and expanded to reflect the latest developments; each chapter reviews the origins, leaders, beliefs, rituals and practices of a NRM, highlighting the specific controversies surrounding each group. A fully updated, revised and expanded edition of an unparalleled introduction to cults and new religious movements. Profiles a number of the most visible, significant, and controversial new religious movements, presenting each group's history, doctrines, rituals, leadership, and organization. Offers a discussion of the major controversies in which new religious movements have been involved, using each profiled group to illustrate the nature of one of those controversies. Covers debates including what constitutes an authentic religion, the validity of claims of brainwashing techniques, the implications of experimentation with unconventional sexual practices, and the deeply rooted cultural fears that cults engender. New sections include methods of studying new religions in each chapter as well as presentations on'groups to watch''--
'An overview of the development of new religions and the controversies surrounding them in late modern society'--
1. Cults and new religions : a primer -- The range of new religious movements -- Controversy and the popular perception of new religious movements -- 2. The Church of Scientology : the question of religion -- L. Ron Hubbard and the origins of Scientology -- Beliefs and practices of the Church of Scientology -- The organizational structure of the Church of Scientology -- Researching Scientology -- 3. Transcendental Mediation : the questions of science and therapy -- Maharishi Mahesh Yogi and the arrival of Transcendental Meditation -- Beliefs and practices of Transcendental Meditation -- The growth and development of Transcendental Meditation -- Researching Transcendental Meditation -- 4. Ramtha and the New Age : the question of'dangerous cult' -- Who is JZ Knight and who is Ramtha? -- History and development of Ramtha's School of Enlightenment -- Beliefs and practices of Ramtha's School of Enlightenment -- RSE and the question of the'dangerous cult' -- Researching Ramtha -- 5. The Unification Church/The Family Federation : the brainwashing/deprogramming controversy -- Sun Myung Moon : savior from the East -- Doctrinal beliefs and ritual practices of the Unification Church -- The growth and organization of the Unification Church outside of Korea -- Brainwashing, deprogramming, and the Unification Church -- Researching the Unification Church -- 6. The Children of God/The Family International : the issue of sexuality -- Mo : David Berg and the origins of the Children of God -- Social organization of the Children of God/The Family -- Beliefs, rituals, and practices of the Children of God/The Family -- The Children of God/The family and the issue of sexuality -- Researching the Children of God/The Family -- 7. The Branch Davidians : the question of cults, media, and violence, part I -- The historical development of the Branch Davidians -- Beliefs and practices of the Branch Davidians under David Koresh -- The siege at Waco and the problem of mass media -- Researching the Branch Davidians -- 8. Heaven's Gate : the question of cults and violence, part II -- Ti, Do, and the origins of Heaven's Gate -- Beliefs and practices of Heaven's Gate -- Recruitment and social organization in Heaven's Gate -- The evolutionary level above humans : new religions, violence, and the media -- Researching Heaven's Gate -- 9. Wicca and witchcraft : confronting age-old cultural fears -- Gerald Gardner and the origins of modern witchcraft -- Social organization and development of modern witchcraft and Wicca -- Beliefs, rituals and practices of modern witchcraft and Wicca -- Satanic panic : the legacy of religious cult fears -- Researching modern Paganism -- 10. Rethinking cults : the significance of new religious movements -- Two perspectives : cults versus new religious movements -- New religions as experimental faiths.
Includes bibliographical references and index.
Keywords: Religions; Cults